Concussive brain trauma : neurobehavioral impairment and maladaptation - Parker, Rolland S. (Boca Raton, Fl. : CRC Press, 2012)
'Continuing the tradition of the bestselling first edition, this second edition provides comprehensive coverage of neurobehavioral disorders in children and adults following impact and acceleration accidents. Completely revised and updated, the book includes comprehensive coverage of consciousness including normal, acute, and persistent alterations. Drawing on his training, education, and experience in human physiology, neuroanatomy, and endocrinology, the author not only gives readers a solid foundation for understanding, diagnosing, and treating concussive brain trauma, but also gives them tools to increase standards of care'--Provided by publisher.
Includes bibliographical references (pages 763-839) and index.
Keywords: Brain -- Concussion; Brain damage